Short‐term pretreatment with a dual 5α‐reductase inhibitor before bipolar transurethral resection of the prostate (B‐TURP): evaluation of prostate vascularity and decreased surgical blood loss in large prostates. (21st January 2015) - Busetto, Gian Maria; Giovannone, Riccardo; Antonini, Gabriele; Rossi, Antonella; Del Giudice, Francesco; Tricarico, Stefano; Ragonesi, Giulia; Gentile, Vincenzo; De Berardinis, Ettore
<x xml:space="preserve">Abstract</x> Objective To investigate if short‐term treatment with dutasteride (8 weeks) before bipolar transurethral resection of the prostate (B‐TURP) can reduce intraoperative bleeding, as dutasteride a dual 5α‐reductase inhibitor (5‐ARI) blocks the conversion of testosterone into its active form dihydrotestosterone (DHT), and reduces prostate volume and prostate‐specific antigen (PSA) levels, while increasing urinary flow rate. Patients and Methods In all, 259 patients were enrolled and randomised to two groups: Group A, receiving placebo and Group B, receiving dutasteride (0.5 mg daily for 8 weeks). Blood samples were taken before and after B‐TURP for serum chemistry evaluation. In particular we evaluated blood parameters associated with blood loss [haemoglobin (Hb) and haematocrit (Ht)] and prostate vascularity [vascular endothelial growth factor (VEGF) immunoreactivity and microvessel density (MVD) using cluster of differentiation 34 (CD34) immunoreactivity]. Results Total testosterone, DHT, PSA level and prostate volume were evaluated and with the exception of DHT and PSA level there was no statistically significant differences between the groups. When comparing changes in Hb and Ht between Group A and Group B before and after B‐TURP, there was a statistically significant difference only in patients with large prostates of ≥50 mL (ΔHb 3.86 vs 2.05 g/dL and ΔHt 4.98 vs 2.64%, in Groups A and B, respectively). There was no significant difference in MVD and VEGF index in prostates of <50 mL, conversely in large prostates the difference become statistically significant. Conclusions Dutasteride was able to reduce operative and perioperative bleeding only in patients with large prostates (≥50 mL) that underwent B‐TURP. Our findings are confirmed by Hb and Ht values reported before and after the B‐TURP and reductions in the molecular markers for VEGF and CD34 in the dutasteride‐treated specimens.